The psychological impact of cybercrime victimization: The importance of personal and circumstantial factors - Borwell, Jildau (European journal of criminology, 2025)
This study examines the psychological impact of cybercrime victimization through the theoretical concepts of the democratization of victimization, coping, and cyborg theory. Using survey data from 2,415 Dutch cybercrime victims it explores how personal and circumstantial factors influence victims? emotional well-being and sense of security. The findings indicate that older victims experience a greater impact on their sense of security, while emotional well-being is more adversely affected in victims who live alone, women, religious victims, and those with lower socioeconomic status. Additionally, specific crime-related factors, namely device hacking and crime duration, are associated with higher impact on both emotional well-being and sense of security. Beyond its academic and theoretical contributions, this study provides valuable insights for developing targeted prevention and support measures for cybercrime victims.